2015
DOI: 10.1017/s0142716415000326
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions as predictors of syntactic awareness in English monolingual and English–Spanish bilingual language brokers and nonbrokers

Abstract: Executive function (EF) skills (cognitive flexibility, inhibition, and working memory) and syntactic awareness of monolingual (English) and bilingual (English–Spanish) language brokers and nonbrokers were examined. EF skills may be salient for brokers, who must not only inhibit interference from another language but also exhibit EF skills when translating. The brokers displayed better cognitive flexibility when compared to the other groups. For the bilingual groups, cognitive flexibility was also a predictor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 82 publications
(205 reference statements)
1
8
0
Order By: Relevance
“…Specifically, in terms of agrammatical word order violations versus asemantical word order violations (i.e., those with a semantic anomaly), Davidson et al (2010) found that bilingual children were better than monolingual children at detecting these types of violations. Others, however, found no significant differences between monolingual and bilingual children when children were asked to detect a semantic anomaly on a syntactic awareness task (Rainey et al, 2016), suggesting a similar lack of differences will be found in the present research. 5.…”
Section: Syntactic Awareness and Cross-linguistic Influencesupporting
confidence: 83%
See 2 more Smart Citations
“…Specifically, in terms of agrammatical word order violations versus asemantical word order violations (i.e., those with a semantic anomaly), Davidson et al (2010) found that bilingual children were better than monolingual children at detecting these types of violations. Others, however, found no significant differences between monolingual and bilingual children when children were asked to detect a semantic anomaly on a syntactic awareness task (Rainey et al, 2016), suggesting a similar lack of differences will be found in the present research. 5.…”
Section: Syntactic Awareness and Cross-linguistic Influencesupporting
confidence: 83%
“…These latter sentences were those that included a semantic anomaly (i.e., "The table set the girl."). Although only the first type of sentence is a 'pure' word order violation, more recent research has suggested that sentences with a semantic anomaly also pose a word order violation (e.g., Barac & Bialystok, 2012;Rainey, Davidson, & Li-Grining, 2016). By presenting both types of sentences, we could more thoroughly assess monolingual and bilingual children's ability to detect these types of word order violations.…”
Section: Syntactic Awareness and Cross-linguistic Influencementioning
confidence: 99%
See 1 more Smart Citation
“…By virtue of being more “practiced” in translation per se, or more practiced in handling different types of domains, one may expect that language brokering could lead to greater sensitivity to nuances of meaning, and easier retrieval of translation equivalents. Despite some early work on “natural translators” (e.g., Malakoff & Hakuta, 1991), there has been little empirical investigation of the potential cognitive and linguistic repercussions of informal translation practice, Indeed, there are currently only a handful of published studies that have compared the performance of informal translators (language brokers) and bilinguals without brokering experience (Garcia et al, 2014; López & Vaid, 2017; Rainey, Davidson & Li-Grining, 2015; Vaid & López, 2014; Vaid, López & Martinez, 2015). The present research sought to fill this gap.…”
mentioning
confidence: 99%
“…Most, however, have focused on syntactic awareness in general and not morphosyntactic awareness specifically, or have not separated syntactic from morphosyntactic constructions on the awareness measure. In particular, several studies have shown that heritage language children perform more poorly on these measures than monolingual children (e.g., Da Fontoura & Siegel, 1995;Lipka, Siegel & Vukovic, 2005), whereas other studies have found that heritage language children either perform the same (Simard et al, 2013) or better than monolingual children (e.g., Bialystok, 1986;Cromdal, 1999;Davidson et al, 2010;Foursha-Stevenson & Nicoladis, 2011;Rainey, Davidson & Li-Grining, 2015). A number of reasons may explain these mixed findings, including both task and individual characteristics.…”
Section: Importance Of Morphosyntactic Awareness In Monolingual and Hmentioning
confidence: 98%